Penerapan Metode Pembelajaran Two Stay Two Stray (TSTS) untuk Meningkatkan Hasil Belajar Siswa pada Materi Budaya Hidup Sehat di Tingkat Sekolah Dasar Negeri 110 Pekanbaru - Indah Permata; Aref Vai; Wedi S (Departement of Mathematics Education, 2023)
This model can be used during the teaching process, one of which is cooperative learning. However, this model emphasizes students to learn in discussion forums, to exchange opinions. In this study using the Two Stay Two Stray method, this method directly involves students to be always active during the learning process. The purpose of this learning method is to improve the spirit of working together, helping each other, being mutually responsible for the tasks that have been given. If this learning method can be used correctly it is hoped that it can increase student enthusiasm during learning, so that with the enthusiasm for learning it can be easy to achieve learning goals. As for the type of research used using quantitative research and in the selection of data collection techniques used using observation, tests and documentation. The samples used in this study were 37 students in VA class and 38 students in VB class. After this learning is applied, it can be concluded that the results of the research show that the achievement of VA class students has increased in terms of individual student learning outcomes and has increased in classical learning outcomes. Whereas in class VB there was an increase in learning achievement both individually, but did not experience classical learning mastery.